PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DI SMA NEGERI 8 LUWU TIMUR - Ema Selfiana (Guru Membangun, 2023)
The learning model is a method used so that student learning activities and achievements can change for the better, one of which is using the Discovery Learning model. The purpose of this research is to increase the activity and learning outcomes of Biology by applying the Discovery Learning model in class XII IPA2 SMA Negeri 8 Luwu Timur, Academic Year 2021/2022. The type of research used is Classroom Action Research (PTK) conducted in 2 cycles. The subjects in this study were class XII IPA2, totalling 35 people. The instruments used were observation sheets for observing student activities and learning outcomes tests in the form of multiple-choice questions. The results of the study showed that student activity data increased from cycle I to cycle II. The learning outcomes of class XII IPA2 SMA Negeri 8 Luwu Timur in cell division material from an average value of 76 in cycle I increased to 85.14 in cycle II and the indicator of success increased from 57.18% in cycle I to 82 .85% in cycle II. It was concluded that the Discovery Learning Model can increase student learning activities and outcomes with an Indicator of success exceeding 80%